2008
DOI: 10.1038/cdd.2008.175
|View full text |Cite
|
Sign up to set email alerts
|

A p53-CBP/p300 transcription module is required for GAP-43 expression, axon outgrowth, and regeneration

Abstract: Transcription regulates axon outgrowth and regeneration. However, to date, no transcription complexes have been shown to control axon outgrowth and regeneration by regulating axon growth genes. Here, we report that the tumor suppressor p53 and its acetyltransferases CBP/p300 form a transcriptional complex that regulates the axonal growth-associated protein 43, a wellcharacterized pro-axon outgrowth and regeneration protein. Acetylated p53 at K372-3-82 drives axon outgrowth, GAP-43 expression, and binds specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
133
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(138 citation statements)
references
References 45 publications
5
133
0
Order By: Relevance
“…However, recent experimental evidence 32 and our own work using HDAC class I and HDAC class I and II inhibitors 33 has proven this to be insufficient in producing postlesion regeneration of sensory fibres following a spinal or optic nerve injury and therefore unlikely the key to unlocking the molecular mechanisms of regeneration. While our work here describes that specific epigenetic codes are induced endogenously following a conditioning lesion that leads to CNS regeneration, it is also consistent with previous findings from our laboratory that showed the presence of a transcriptional complex formed by p53, p300 and PCAF in the proximity of several RAGs including GAP-43, Coronin 1b and Rab13 in primary neurones as well as facial motor neurones in a PNS facial nerve axotomy model [34][35][36] . Additionally, we found that the histone acetyltransferase p300 (which may form a complex with PCAF) is developmentally regulated in retinal ganglion cells and whose overexpression drives axonal regeneration of the injured optic nerve 33 .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, recent experimental evidence 32 and our own work using HDAC class I and HDAC class I and II inhibitors 33 has proven this to be insufficient in producing postlesion regeneration of sensory fibres following a spinal or optic nerve injury and therefore unlikely the key to unlocking the molecular mechanisms of regeneration. While our work here describes that specific epigenetic codes are induced endogenously following a conditioning lesion that leads to CNS regeneration, it is also consistent with previous findings from our laboratory that showed the presence of a transcriptional complex formed by p53, p300 and PCAF in the proximity of several RAGs including GAP-43, Coronin 1b and Rab13 in primary neurones as well as facial motor neurones in a PNS facial nerve axotomy model [34][35][36] . Additionally, we found that the histone acetyltransferase p300 (which may form a complex with PCAF) is developmentally regulated in retinal ganglion cells and whose overexpression drives axonal regeneration of the injured optic nerve 33 .…”
Section: Discussionsupporting
confidence: 77%
“…RNA was extracted using PeqGOLD TriFast reagent (peqlab), cDNA was synthesized from 1 mg of total RNA using both oligodT and random hexamers from the SuperScript II Reverse Transcriptase kit (Invitrogen) and a real time RT-PCR was performed using Absolute QPCR SYBR low ROX master mix (Thermo Scientific). Quantities and fold changes were calculated following the manufacturer's instructions (ABI 7,500) and as previously reported 35,43 . Primer sequences are shown in Supplementary Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously found that p53 can occupy the promoters and drive the expression of a number of genes involved in neurite and axonal outgrowth such as Coronin 1b, Rab13 (Di , and GAP-43 (Tedeschi et al, 2009a;Floriddia et al, 2011). Moreover, p53 transcriptionally enhances the expression of cGKI, thereby inhibiting semaphorin 3A-dependent growth cone collapse in primary cortical and dorsal root ganglia neurons (Tedeschi et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic modification of histones and DNA at these sites can also be simultaneously monitored. A similar protocol can be performed following facial nerve lesion, where the facial nerve nuclei can be dissected from the brainstem and processed by ChIP as we previously reported (Tedeschi et al, 2009). …”
Section: Discussionmentioning
confidence: 99%